The DEVELOPMENT OF INTERACTIVE E-MODULES ASSISTED WITH CANVA AND PROFESSIONAL FLIP PDF ON OPPORTUNITY MATERIALS - Virda Putri Novita Wulandari; Dian Devita Yohanie; Darsono (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
This research aims to determine the results of the validity and practicality of developing interactive e-modules assisted by Canva and Flip PDF Professional on Opportunity material for class X SMA. The type of research used is Research and Development (R&D) with the ADDIE development model which includes five stages: analysis, design, development, implementation, and evaluation. The research results show that the e-module product developed is included in the "very valid" and "very practical" categories. Validation was carried out by four validators, with percentage validity results: material expert (83%), lecturer media expert 1 (95%), lecturer media expert 2 (95%), and practitioner expert (90%), resulting in an average validity of 90 .75%. The implementation of a trial limited to 10 students showed a practicality level of 87.05%. Evaluation is carried out based on validator suggestions, resulting in improvements to media and material aspects. Thus, the interactive e-module developed is valid and practical for use in mathematics learning, facilitating students to learn independently and increasing active involvement in the learning process.